2015
DOI: 10.1152/ajpheart.00469.2015
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training in chronic heart failure: improving skeletal muscle O2transport and utilization

Abstract: Hirai DM, Musch TI, Poole DC. Exercise training in chronic heart failure: improving skeletal muscle O 2 transport and utilization. Am J Physiol Heart Circ Physiol 309: H1419 -H1439, 2015. First published August 28, 2015; doi:10.1152/ajpheart.00469.2015.-Chronic heart failure (CHF) impairs critical structural and functional components of the O 2 transport pathway resulting in exercise intolerance and, consequently, reduced quality of life. In contrast, exercise training is capable of combating many of the CHF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
159
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(167 citation statements)
references
References 340 publications
4
159
0
4
Order By: Relevance
“…Endurance training has been recommended for cardiac patients [42]. In our study we found that the maximal oxygen uptake increased equally in both groups.…”
Section: Discussionsupporting
confidence: 63%
“…Endurance training has been recommended for cardiac patients [42]. In our study we found that the maximal oxygen uptake increased equally in both groups.…”
Section: Discussionsupporting
confidence: 63%
“…Moreover, in obese older patients with chronic heart failure with preserved ejection fraction, 20 weeks of diet and exercise had additive effect in increasing peak oxygen consumption, a functional recovery that positively correlated with the increase in lean body mass and with the improvement in thigh muscle quality (muscle/intermuscular fat ratio) (Kitzman et al, 2016). In this sense, beneficial effects of exercise in chronic heart failure patients seem to be related to the improvement in skeletal muscle oxygen delivery and utilization (Hirai et al, 2015). The positive impact of exercise is not restricted to heart failure since exercise training in patients with chronic pulmonary hypertension is associated with a significant improvement in physical performance, pulmonary arterial pressure and quality of life (Pandey et al, 2015).…”
Section: Article In Pressmentioning
confidence: 96%
“…Endurance exercise training promotes several cardiovascular and muscular benefits in CHF and aging [184,185], including improvements in inspiratory muscle function in CHF [186]. Endurance training prevents the loss of diaphragm specific force in animals with CHF with preserved ejection fraction or after injection of TNF-α [187,149].…”
Section: Therapeutic Strategies To Counteract Inspiratory Dysfunctionmentioning
confidence: 99%